Electronic structure models of phosphorus 0-doped silicon - Carter, Damien; Warschkow, O.; Marks, Nigel; McKenzie, D. (American Physical Society, 2009)
We report a density-functional theory treatment of phosphorus 0-doped silicon. Using large asymmetric unit cells with up to 800 atoms, we obtain first-principles doping potentials, band energies, and donor-electron distributions. The explicit and nonempirical description of both valence and donor electrons improves upon previous models of this system. The effects of overlapping 0-doping potentials in smaller systems are adequately captured using a uniform band alignment shift.